Volunteer Movement in Rural Areas of RSFSR During Great Patriotic War: A Historical and Economic Analysis (Materials from Rostov Region) - V. A. Bondarev (Научный диалог, 2025)
This study examines the economic aspects of the volunteer movement in rural areas of the Russian Soviet Federative Socialist Republic (RSFSR) during the Great Patriotic War, focusing on the Rostov region as one of Russia's historically agrarian territories. The research is grounded in both published and archival materials. It explores the influence of the collective farm system, established in the USSR throughout the 1930s, on the volunteer movement. The findings reveal that collective farms emerged as a crucial factor in wartime volunteering. The significance of these collective enterprises is highlighted in their role in organizing and supplying volunteer Cossack cavalry units formed in the Rostov region during the Great Patriotic War. Unlike pre-Soviet practices, collective farms enabled the provision of essential equipment and supplies to Cossack cavalrymen without causing significant material hardship for the families of volunteer Cossacks. The study notes that, thanks to the high mobilization potential of collective farms, Cossack cavalry units received necessary reinforcements in personnel and horses, maintaining their combat effectiveness throughout the war years. The role of collective farms in organizing voluntary material support for the front is highly valued, with collective farmers processing additional “defense hectares” and collecting donations for the active army in the form of money, food, clothing, and other goods.